2004
DOI: 10.3168/jds.s0022-0302(04)73187-2
|View full text |Cite
|
Sign up to set email alerts
|

A Complete Genome Scan of the Israeli Holstein Population for Quantitative Trait Loci by a Daughter Design

Abstract: Eleven Israeli Holstein families including 5221 cows were analyzed by a daughter design for eight economic traits: milk, fat and protein production, fat and protein percentage, somatic cell score (SCS), herd-life, and female fertility. The cows were genotyped for 73 microsatellites with maximum spacing between markers of 53 cM. There were 86,304 informative genotypes. Preliminary analysis was by ANOVA of each trait, with the marker effect nested within sire. Significance was determined by controlling the false… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
39
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 32 publications
6
39
0
Order By: Relevance
“…Casas and Stone (2006), analyzing the information of the half-sib family sired by BH used in the present study, identified a QTL associated with the probability of contracting infectious bovine keratoconjunctivitis in a region simi- 75.0 X X X X lar to the one in the present study. Quantitative trait loci for somatic cell score have been detected on bovine chromosome 20 (Rodriguez-Zas et al, 2002;Ashwell et al, 2004;Ron et al, 2004). Rodriguez-Zas et al (2002) detected a QTL for somatic cell score on the centromeric region of chromosome 20.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Casas and Stone (2006), analyzing the information of the half-sib family sired by BH used in the present study, identified a QTL associated with the probability of contracting infectious bovine keratoconjunctivitis in a region simi- 75.0 X X X X lar to the one in the present study. Quantitative trait loci for somatic cell score have been detected on bovine chromosome 20 (Rodriguez-Zas et al, 2002;Ashwell et al, 2004;Ron et al, 2004). Rodriguez-Zas et al (2002) detected a QTL for somatic cell score on the centromeric region of chromosome 20.…”
Section: Discussionmentioning
confidence: 99%
“…A plethora of QTL on different chromosomes have been detected and associated with somatic cell score and mastitis in dairy cattle (Rodriguez-Zas et al, 2002;Ashwell et al, 2004;Ron et al, 2004). Gasparin et al (2007), using an F 2 population of cattle derived from Bos taurus and Bos indicus, identified putative QTL for ectoparasite resistance on chromosomes 5, 7, and 14.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Understanding the mixture distribution allows us to version of the "daughter design" developed by animal breeders (Weller et al 1990; Bovenhuis and Weller develop an exact EM algorithm for solving the MLE. We were able to define x 1j ϭ m Ϫ1 j (m 11 Ϫ m 22 ) and x 2j ϭ 1994; Mackinnon and Weller 1995;Ron et al 2001). We learned that the daughter design can be more effim Ϫ1 j m 12 and further take advantage of the multinomial distribution of the m's.…”
Section: Multiple-qtl Analysismentioning
confidence: 99%
“…It is even possible to for low heritability traits in animals by using the daughgenotype plants in generation x and phenotype plants ter design (Weller et al 1990; Bovenhuis and Weller in generation y to conduct QTL mapping. This design 1994; Mackinnon and Weller 1995;Ron et al 2001), is called the F x :y design for y Ն x (Fisch et al 1996; Jiang where the phenotypic value of the sire has been replaced and Zeng 1997; Chapman et al 2003). This generalized by the mean phenotypic value of the daughters.…”
mentioning
confidence: 99%